Construction of indenols and derivatives through Rh(III) catalyzed CH activation in a one-pot manner. (28th September 2022) - Wu, Zhouping; Lin, Zheng; Tang, Jiangyan; Lv, Shan; Huang, Tianle; Shi, Yuesen; Chen, Jian; Hai, Li; Wu, Yong
Graphical abstract: Abstract: Transition-metal catalyzed CH activation has become a useful tool to achieve compounds. Divergent one-pot multi-step cascade construction has improved the efficiency of building complex molecules. Here we have developed the construction of indenols and derivatives through Rh(III) catalyzed CH activation in a one-pot manner by simply tuning the reaction conditions.